Tuning the electric dipole transitions (5D0 → 7F2 and 5D0 → 7F4) in thin Eu-doped BiOCl nanosheets - Singh, Dinesh; Poddar, Pankaj (Journal of Physical Chemistry C, 2026)
The polarization and depolarization of layered ferroelectric materials can be tuned by altering the thickness of nanosheets, apart from controlling inter/intralayer distances, doping of ions, the surrounding dielectric environment, etc. In two-dimensional, single-crystalline ferroelectric nanosheets, the reduction in the thickness facilitates the internal electric field (IEF), which leads to enhanced depolarization. BiOCl is a layered ferroelectric material with repeating layers of [Bi2O2](2+), which exhibit anisotropy. However, the depolarization and polarization of BiOCl are significantly influenced by the thicknesses of its nanosheets. Herein, 1-dodecanethiol-capped europium (Eu3+)-doped BiOCl thin nanosheets resembling a two-dimensional structure have been synthesized using the solid-state grinding method at ambient temperature. As a result of the depolarization effect, the strength of the electric dipole transitions D-5(0) -> F-7(2) and D-5(0) -> F-7(4) increases in the Eu-doped BiOCl nanosheets. However, thiol capping helps in synthesizing uniform 2D nanosheets with reduced vertical dimensions (thickness near 15-30 nm). It is observed that all of the prepared samples with varying Eu ion concentrations show uniform nanosheet-like morphology, as confirmed by electron microscopy (FESEM and HRTEM). As the concentration of Eu ions increases in the BiOCl host lattice, the intensity of electric dipole transitions also increases (until 9 mol %). Fourier transform infrared spectroscopy (FT-IR) reveals the coating of 1-dodecanthiol on the Eu-doped BiOCl molecule. Furthermore, the Eu-doped BiOCl samples showed prominent far-red emission at 700 nm, corresponding to the D-5(0) -> F-7(4) transition. Moreover, this work emphasizes the synthesis of Eu-doped phosphor at an ambient temperature of 24 +/- 2 degrees C and generates a deeper understanding of the abnormal electric dipole (D-5(0) -> F-7(4)) transition.